Gender Differences in Perceptions of Technology, Technology Readiness, and Spatial Cognition. (December 2020) - Blasko, Dawn G.; Lum, Heather C.; Campbell, John
With developments in new technologies such as mobile mapping and mixed reality (virtual and augmented reality), there is demand for insight into how individual differences influence technology readiness. We examined the influence of gender, perceived sense of direction, mental rotation, and navigation on the different aspects of technology readiness: discomfort, optimism, innovativeness, and insecurity. The results of an online questionnaire showed that women were equally optimistic about embracing technology. However, they rated themselves higher on discomfort and insecurity and lower on innovativeness. We also examined the perceived usefulness of navigation aids. For example, both men and women found mobile maps useful, but men found paper maps more useful than women. Women were more likely than men to feel that using Google Maps increased safety. Therefore, it is incorrect to say that women are less ready to embrace technology, rather it depends on its usefulness for the task at hand.